The Effect Of Qardh Fund Distribution At The Infaq Bank On Customer Welfare - Pujakesuma, Dedi; Firdaus, Achmad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Customer welfare is the primary goal of Islamic social finance, making its improvement a key concern. This study examines the impact of infaq fund distribution through the Qardh contract by Bank Infaq Masjid Raya Bintaro Jaya on customer welfare. The main variables include infaq fund distribution, tabarru’ funds as ta’awun funds to address payment defaults and risk mitigation strategies. The research employs a quantitative method using SEM-PLS analysis, complemented by interviews with the bank’s management. The findings indicate that although the contribution of infaq fund distribution to societal welfare is structurally low, effective management of tabarru’ funds and risk mitigation strategies can enhance the well-being of beneficiaries. Therefore, it is recommended that Bank Infaq enhance Sharia financial literacy among its customers to maximize the positive impact of the Qardh financing program.